Effects of Iron Oxide Nanoparticles on Foliage Development of Red Radish (Raphanus sativus) and Bok Choy (Brassica rapa) - Duong, Thi Huong; Kurihara, Takaaki; Inagaki, Yoshihiko; Sakakibara, Yutaka; Dang, Minh Hieu (Old Journal, 2018)
Nanomaterials have been used in many applications covering many different aspects in life. Among nanomaterials, iron oxide nanoparticles (FeNPs) have been considered relatively safe, and appeared in a number of applications from medical, health to environmental applications. This booming in using FeNPs leads to the appearance of them in different water bodies that might end up lately in plants and animals. This study reports on the effects of FeNPs on foliage development of two common vegetables, red radish (Raphanus sativus) and bok choy (Brassica rapa). It showed that radish was not affected by the nanoparticles regardless of exposure scenarios. The developmental rate of bok choy, however, showed increase with FeNPs concentration in the scenario that seeds were pre-soaked in water before sowing on medium containing FeNPs. In the experimental scenario that seeds were soaked in solutions containing FeNPs before sowing on nanoparticle-free medium, it showed retardation in the developmental rate of the seeds.